Ultra-fast and compact all-optical encoder based on photonic crystal nano-resonator without using nonlinear materials - Olyaee, Saeed (Photonics Letters of Poland, 2019)
In this paper an ultra-compact all-optical encoder is presented by using a two-dimensional photonic crystal. The designed logic gate is based on the interference effect. The proposed structure consists of several photonic crystal waveguides connected by 2 nano-resonators. The nano-resonators are designed to reduce the size of the radius of the dielectric rods. The contrast ratios and delay time for the proposed all-optical encoder are respectively 6 dB and 125 fs. The size of the structure is equal to 132 µm2. Equality of the output power in the logic states “one”, the small dimensions, the low delay time, compact and simple structure have shown that the logic gate is suitable for the using in optical integrated circuits. Full Text: PDF References A. Salmanpour, Sh. Mohammadnejad, A. Bahrami, "Photonic crystal logic gates: an overview", Optical and Quantum Electronics. 47, 2249 (2015). CrossRef S. C. Xavier, B. E. Carolin, A. p. Kabilan, W. Johnson, "Compact photonic crystal integrated circuit for all-optical logic operation", IET Optoelectronics. 10, 142 (2016). CrossRef Y. Miyoshi, K. Ikeda, H. Tobioka, T. Inoue, S. Namiki, K. Kitayama, "Ultrafast all-optical logic gate using a nonlinear optical loop mirror based multi-periodic transfer function", Optics Express. 16, 2570 (2008). CrossRef D. K. Gayen, A. Bhattachryya, T. Chattopadhyay, J. N. Roy, "Ultrafast All-Optical Half Adder Using Quantum-Dot Semiconductor Optical Amplifier-Based Mach-Zehnder Interferometer", Journal of Lightwave Technology. 30, 3387 (2012). CrossRef A. Mohebzadeh-Bahabady, S. Olyaee, "All-optical NOT and XOR logic gates using photonic crystal nano-resonator and based on an interference effect", IET Optoelectronics. 12, 191 (2018). CrossRef Z. Mohebbi, N. Nozhat, F. Emami, "High contrast all-optical logic gates based on 2D nonlinear photonic crystal", Optics Communications. 355, 130 (2015). CrossRef M. Mansouri-Birjandi, M. Ghadrdan, "Full-optical tunable add/drop filter based on nonlinear photonic crystal ring resonators", Photonics and Nanostructures-Fundamentals and Applications. 21, 44 (2016). CrossRef H. Alipour-Banaei, S. Serajmohammadi, F. Mehdizadeh, "Effect of scattering rods in the frequency response of photonic crystal demultiplexers", Journal of Optoelectronics and Advanced Materials. 17, 259 (2015). DirectLink A. Mohebzadeh-Bahabady, S. Olyaee, H. Arman, "Optical Biochemical Sensor Using Photonic Crystal Nano-ring Resonators for the Detection of Protein Concentration", Current Nanoscience. 13, 421 (2017). CrossRef S. Olyaee, A. Mohebzadeh-Bahabady, "Designing a novel photonic crystal nano-ring resonator for biosensor application", Optical and Quantum Electronics. 47, 1881 (2015). CrossRef F. Parandin, R. Malmir, M. Naseri, A. Zahedi, "Reconfigurable all-optical NOT, XOR, and NOR logic gates based on two dimensional photonic crystals", Superlattices and Microstructures. 113, 737 (2018). CrossRef F. Mehdizadeh, M. Soroosh, H. Alipour-Banaei, "Proposal for 4-to-2 optical encoder based on photonic crystals", IET Optoelectronics. 11, 29 (2017). CrossRef M. Hassangholizadeh-Kashtiban, R. Sabbaghi-Nadooshan, H. Alipour-Banaei, "A novel all optical reversible 4 × 2 encoder based on photonic crystals", Optik. 126, 2368 (2015). CrossRef T. A. Moniem, "All-optical digital 4 × 2 encoder based on 2D photonic crystal ring resonators", Journal of Modern Optics. 63, 735 (2016). CrossRef S. Gholamnejad, M. Zavvari, "Design and analysis of all-optical 4–2 binary encoder based on photonic crystal", Optical and Quantum Electronics. 49, 302 (2017). CrossRef H. Seif-Dargahi, "Ultra-fast all-optical encoder using photonic crystal-based ring resonators", Photonic Network Communications. 36, 272 (2018). CrossRef S. Olyaee, M. Seifouri, A. Mohebzadeh-Bahabady, and M. Sardari, "Realization of all-optical NOT and XOR logic gates based on interference effect with high contrast ratio and ultra-compacted size", Optical and Quantum Electronics. 50, 12 (2018). CrossRef C. J. Wu, C. P. Liu, Z. Ouyang, "Compact and low-power optical logic NOT gate based on photonic crystal waveguides without optical amplifiers and nonlinear materials", Applied Optics.51, 680 (2012). CrossRef Y. C. Jiang, S. B. Liu, H. F. Zhang, X. K. Kong. "Realization of all optical half-adder based on self-collimated beams by two-dimensional photonic crystals", Optics Communications. 348, 90 (2015). CrossRef A. Salmanpour, S. Mohammadnejad, P. T. Omran, "All-optical photonic crystal NOT and OR logic gates using nonlinear Kerr effect and ring resonators", Optical and Quantum Electronics. 47, 3689 (2015). CrossRef E. H. Shaik, N. Rangaswamy, "Single photonic crystal structure for realization of NAND and NOR logic functions by cascading basic gates", Journal of Computational Electronics. 17, 337 (2018). CrossRef